2022
DOI: 10.2991/assehr.k.220102.019
|View full text |Cite
|
Sign up to set email alerts
|

The Problems of Implementation of Multicultural Education Through E-Learning Based History Learning (Case Study of SMAN 1 Natar)

Abstract: This study aims to find out the problems of implementing multicultural education through history learning during the E-Learning period, with a case study of the State High School 1 Natar. The strategy in this research is a case study, the research method used is qualitative, with a descriptive approach. Collecting data through direct observation, interviews with history teachers and students, literature studies in the form of books, journals, archives and documentation. Data were analyzed through data reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, based on the instructors' observations, Form 2 pupils observed that the typical student reported having difficulty recalling historical information (Amali et al, 2022) since there were too many facts to remember. This encourages students to disregard the topic of History since it is boring, difficult to comprehend, and has no direct relevance to their life (Perdana & Ekwandari, 2022), resulting in the passive teaching and learning of History. To solve the issue, instructors and students collaborate to provide a dynamic and engaging curriculum.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Moreover, based on the instructors' observations, Form 2 pupils observed that the typical student reported having difficulty recalling historical information (Amali et al, 2022) since there were too many facts to remember. This encourages students to disregard the topic of History since it is boring, difficult to comprehend, and has no direct relevance to their life (Perdana & Ekwandari, 2022), resulting in the passive teaching and learning of History. To solve the issue, instructors and students collaborate to provide a dynamic and engaging curriculum.…”
Section: Background Of the Studymentioning
confidence: 99%